Humpback Whale (Megaptera novaeangliae) Song on a Subarctic Feeding Ground - Tyarks, Saskia Cathrin; Aniceto, Ana S.; Ahonen, Heidi; Pedersen, Geir; Lindstrøm, Ulf (Frontiers in Marine Science, 2021)
Male humpback whales (Megaptera novaeangliae) are known to produce long complex sequences of structured vocalizations called song. Singing behavior has traditionally been associated with low latitude breeding grounds but is increasingly reported outside these areas. This study provides the first report of humpback whale songs in the subarctic waters of Northern Norway using a long-term bottom-moored hydrophone. Data processed included the months January–June 2018 and December 2018–January 2019. Out of 189 days with recordings, humpback whale singing was heard on 79 days. Singing was first detected beginning of January 2018 with a peak in February and was heard until mid-April. No singing activity was found during the summer months and was heard again in December 2018, continuing over January 2019. A total of 131 song sessions, including 35 full sessions, were identified throughout the study period. The longest and shortest complete sessions lasted 815 and 13 min, respectively. The results confirm that singing can be heard over several months in winter and spring on a high latitude feeding ground. This provides additional evidence to the growing literature that singing is not an explicit behavior confined to low latitude breeding grounds. The peak of song occurrence in February appears to coincide with the reproductive cycle of humpback whales. Finally, this study indicates that song occurrence on a subarctic feeding ground likely aids the cultural transmission for the North Atlantic humpback whale population.